Collaboration, alliance, and merger among higher education institutions - Williams, Jonathan (OECD Publishing, 2017)
Declining student numbers; growing fiscal pressures; and intensified international competition for prestige, research talent and funding, have increasingly made collaborations, alliances, and mergers among higher education institutions a priority for institutions themselves, and for the governments that support them. Collaborations, alliances and mergers among higher education institutions may seek to enhance academic performance, to achieve economic efficiencies, or to better align the network and performance of institutions to public needs. Institutional collaboration occurs less frequently and successfully in the design and delivery of instruction than in other domains, owing largely to the traditionally autonomous and solitary role of faculty in this area. Collaboration is much more common in research, engagement, and back-end administration and other supports, with research collaboration often offering the greatest performance gains, and administrative collaboration the greatest potential efficiencies. Targeted grants are the most common tool governments use to encourage institutional collaboration and consolidation, while more flexible quality assurance standards and the greater alignment of policy frameworks more generally can also make it much easier for institutions to collaborate. Evidence about the outcomes of collaborations, alliances, and mergers is limited, but indicates that these initiatives can strengthen institutional performance, produce efficiencies, improve resilience and enhance alignment to national priorities, although not for all institutions in all circumstances. Policymakers who succeed in promoting effective collaboration appear to strategically stimulate institutional initiative, support effective planning and implementation, secure stakeholder buy-in, concentrate resources, and achieve policy alignment
Keywords: Education